(untitled) (Research, Society and Development, 2022)
The success of endodontic treatment depends on a good sealing of the root canal to avoid possible infiltration and contamination of the periradicular tissues. One of the functions of endodontic cement is to fill the empty spaces between the gutta-percha cones and the dentinal walls, which improves the quality of the filling. The adequate radiopacity of endodontic cements helps in their correct visualization in the canal. Allowing the detection of condensation failures and allowing an adequate evaluation of the endodontic treatment. The radiopacity of these materials must follow international standards established by the American Dental Association and ISO standards. The aim of this study was to evaluate the radiopacity of endodontic cements using digital radiographs. And for that, three endodontic cements were selected: Endofill, Bio-C cement and MTA Fillapex. Ten specimens were made for all cements of three mm in diameter by two mm in thickness. Each sample was radiographed together with a five mm diameter and three mm thick aluminum disc, using a digital radiographic sensor. The images obtained were read with the Image j program, evaluating the gray scale. The values ​​obtained were compared with ISO standards according to specification 57 of ISO/ADA 6876:2012. The results showed that all cements evaluated meet ADA specifications and ISO standards. No statistical difference was detected between the radiopacity values of Endofill and Bio-C Sealer cements. These showed statistically greater radiopacity than MTA Fillapex.